Strategi manajemen risiko kepatuhan syariah di perbankan syariah dalam dinamika persaingan perbankan digital dan dominasi perbankan konvensional - Buddhi, Savita Mahayu (Maliki Interdisciplinary Journal, 2025)
The rapid development of digitalization has brought significant changes to the financial industry, both conventional and Islamic. This transformation has intensified competition among financial institutions, encouraging Islamic banks to continuously innovate in order to remain competitive amid the dominance of conventional systems. However, such innovation also poses new challenges in the form of compliance risks with Islamic principles. This article aims to analyze and formulate strategies for managing sharia compliance risk within the dynamics of digital banking competition. This study employs a descriptive qualitative approach using a literature review method based on various sources, including academic journals, financial regulations, and relevant literature. The analysis reveals that sharia compliance risk management strategies can be implemented through strengthening the role of the Sharia Supervisory Board (DPS), enhancing sharia literacy among human resources, and applying technology-based financial products that align with Islamic principles. These three aspects serve as the foundation to ensure that digital innovation remains within the boundaries of Islamic law while maintaining public trust in the integrity of Islamic banking.